IMPLEMENTASI ZAKAT SEBAGAI PENDAPATAN ASLI DAERAH - Dahlawi (Al-Ijtima`i: International Journal of Government and Social Science, 2019)
Management of zakat, donations, endowments, other religious assets and supervision of trusteeship in Aceh has not been realized as expected. This research was conducted to further study about the implementation of management carried out by Baitul Mal based on Qanun Number 10 of 2018, especially zakat as Regional Original Revenue (PAD). This study is a qualitative study using in-depth interviews with 11 (eleven) informants who are Baitul Mal Aceh apparatus and related elements, as well as observation and documentation. The results showed that, the implementation of the management of Zakat by Baitul Mal Aceh based on Aceh Qanun Number 10 of 2018 had not been realized optimally, because it was still focused on the management of zakat which was sourced from the income of the government apparatus. Theefforts to better understand about Zakat, PAD and Baitul Mal need to be done through increasing internal and external intensively socialization through mass media and electronic media, meetings and training, seminars, technical guidance, more regular work coordination, professional apparatus placement, adequate work facilities, clear and consistent work rules or SOPs must be followed up with various implementing regulations as a basis for implementing Qanun Number 10 of 2018. It is to adopt the organizational structure, duties, functions, authorities and work system as a single unit in the form of financial management patterns of regional public service center (BLUD) and stipulates zakat as a special PAD. The involvement of informants from relevant government agencies and the community from representatives of the people, academics, scholars of the dayah/pesantren and other general public is needed to obtain more varied research results.